Historical Time, collective memory, and the finitude of historical understanding - Barash, Jeffrey Andrew (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This text focuses on the decline of the traditional conceptions of historical unity which, in different ways, encouraged the philosophies of history, as well as the ideologies that this generated, in the modern period. As a result of the comprehension of the limits of historical understanding which has emerged in an atmosphere of rapid change, the dislocation and discontinuity of the 20th century, the decline of the traditional concepts of historical unity through time have highlighted a new vision of human temporal finitude. According to the idea proposed here, the general interest in collective memory that has appeared in the last few decades is tightly linked with this new temporal perspective. In a current context in which mutation and discontinuity have undermined the long-term vision of the philosophy of history and previous ideologies, the concept of collective memory has become an essential prism through which the possibility of social cohesion over time is refracted. There where the contemporary concern about collective memory is stimulated by a search for group cohesion in the midst of changing collective perspectives, its temporal horizon has been frequently characterized by an immersion in the present or a «presentism». Nevertheless, beyond this limited perspective, lies a new outlook on collective memory and the limited scope of human historical comprehension which allows an emphasis on more complex and more qualified contemporary temporal orientations, which are those this article attempts to highlight.